Mutations Within the Transcription Factor PROP1 in a Cohort of Turkish Patients with Combined Pituitary Hormone Deficiency - Fatma Derya Bulut; Semine Özdemir Dilek; Damla Kotan; Eda Mengen; Fatih Gürbüz; Bilgin Yüksel (Galenos Yayincilik, 2020)
Objective:Mutations of the genes encoding transcription factors which play important roles in pituitary morphogenesis, differentiation and maturation may lead to combined pituitary hormone deficiency (CPHD). PROP1 gene mutations are reported as the most frequent genetic aetiology of CHPD. The aim of this study was to describe the phenotypes of Turkish CPHD patients and define the frequency of PROP1 mutations.Methods:Fifty-seven CPHD patients from 50 families were screened for PROP1 mutations. The patients were affected by growth hormone (GH) and additional anterior pituitary hormone deficiencies.Results:All patients had GH deficiency. In addition, 98.2% had central hypothyroidism, 45.6% had hypogonadotropic hypogonadism, 43.8% had adrenocorticotropic hormone deficiency and 7.1% had prolactin deficiency. Parental consanguinity rate was 50.9% and 14 cases were familial. Mean height standard deviation score (SDS) and weight SDS were -3.8±1.4 and -3.1±2.0, respectively. Of 53 patients with available pituitary imaging, 32 (60.4%) showed abnormalities. None had extra-pituitary abnormalities. Eight index patients had PROP1 gene mutations. Five sporadic patients were homozygous for c.301_302delAG (p.Leu102CysfsTer8) mutation, two siblings had exon 2 deletion, two siblings had complete gene deletion and two siblings were homozygous for the novel c.353A>G (p.Q118R) mutation. The frequency of the PROP1 mutations was 16% in our cohort. Mutation rate was significantly higher in familial cases compared to sporadic cases (42.8% vs 11.6%; p<0.01).Conclusion:Phenotype of patients regarding hormonal deficiencies, pituitary morphology, presence of extra-pituitary findings, family history of CPHD and parental consanguinity are important for deciding which pituitary transcription factor deficiency should be investigated. PROP1 mutation frequencies vary in different populations and its prevalence is high in Turkish CPHD patients.